Interaction with the entomopathogenic fungus Beauveria bassiana influences tomato phenome and promotes resistance to Botrytis cinerea infection - Russo, Assunta; Winkler, Jana Barbro; Ghirardo, Andrea; Monti, Maurilia M.; Pollastri, Susanna; Ruocco, Michelina; Schnitzler, Jörg-Peter; Loreto, Francesco (Frontiers in Plant Science, 2023)
Plants are central to complex networks of multitrophic interactions. Increasing evidence suggests that beneficial microorganisms (BMs) may be used as plant bio-stimulants and pest bio-control agents. We investigated whether tomato (Solanum lycopersicum L.) plants are thoroughly colonized by the endophytic and entomopathogenic fungus Beauveria bassiana, and how such colonization affects physiological parameters and the phenotype of plants grown under unstressed conditions or exposed to the pathogenic fungus Botrytis cinerea. As a positive control, a strain of the well-known biocontrol agent and growth inducer Trichoderma afroharzianum was used. As multitrophic interactions are often driven by (or have consequences on) volatile organic compounds (VOCs) released by plants constitutively or after induction by abiotic or biotic stresses, VOC emissions were also studied. Both B. bassiana and T. afroharzianum induced a significant but transient (one to two-day-long) reduction of stomatal conductance, which may indicate rapid activation of defensive (rejection) responses, but also limited photosynthesis. At later stages, our results demonstrated a successful and complete plant colonization by B. bassiana, which induced higher photosynthesis and lower respiration rates, improved growth of roots, stems, leaves, earlier flowering, higher number of fruits and yield in tomato plants. BeauveriaB. bassiana also helped tomato plants fight B. cinerea, whose symptoms in leaves were almost entirely relieved with respect to control plants. Less VOCs were emitted when plants were colonized by B. bassiana or infected by B. cinerea, alone or in combination, suggesting no activation of VOC-dependent defensive mechanisms in response to both fungi.